Diaspora Investing : The Business and Investment Interests of the Caribbean Diaspora - Dhanani, Qahir (World Bank, Washington, DC, 2014)
The Caribbean region is unique for many reasons. Perhaps most striking among these is the demographic fact that for almost every resident in the region there is an individual living in the diaspora abroad. This near one-to-one ratio of nationals to diaspora members presents a tremendous opportunity for cross-border engagement among a people who share common cultures and histories. This report presents findings from the assessment, including both the quantitative data from the surveys and the qualitative data from focus groups and individual interviews. It aims to help all stakeholders, including policy makers, multilateral financial institutions, donors, and program managers, among others to better understand and engage the Caribbean diaspora. The report also provides material for an open dialogue on new ways to engage the diaspora for investment purposes. Although the assessment is focused primarily on the diaspora members' willingness and ability to invest in and mentor high-potential growth-oriented enterprises (HGEs), it also touches on their interest to be involved through other channels and investment vehicles, such as diaspora bonds, volunteering, or charitable giving.